A fixed charge transportation problem with damageable items under uncertain environment - Zhu, Kai; Ji, Kaiyuan; Shen, Jiayu (Physica A, 2021)
An uncertain mathematical model for a fixed charge transportation problem is created in this paper. To make it closer to actuality, item damage during the transportation is considered. Besides, as some indeterministic factors may appear in the problem because of the incompletion of historical data, several parameters in this model such as purchasing price, supplies, demands and so on are regarded as uncertain variables based on uncertainty theory. After that, the original model is analyzed in two criteria of expected value criterion and chance-constrained one, and two kinds of uncertain models as well as their corresponding deterministic forms are constructed. Then, two intelligent algorithms like the genetic algorithm (GA) and the particle swarm optimization algorithm (PSO) are employed to figure out the equivalent forms of the models. Finally, the applications of the models are displayed via several numerical examples. •Uncertain models for a fixed charge transportation problem are constructed.•The models are transformed into deterministic forms based on uncertainty theory.•Some numerical examples are given to show the applications of the models.